2011
DOI: 10.1111/j.1464-410x.2011.10434.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of degarelix for advanced hormone‐dependent prostate cancer

Abstract: What ' s known on the subject? and What does the study add? The European Medicines Evaluation Agency recognised that the principal advantage of degarelix is the avoidance of the transient rise in testosterone. This paper compares the cost-effectiveness of degarelix with the most common treatment in the UK (LHRHa plus short-term anti-androgen) for the management of prostate cancer, focusing on the costs and clinical consequences that might be associated by the avoidance of the transient rise in testosterone. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…As spinal cord compression is a rare event, data were not available from the trial. Events were incorporated in the same manner as in Lu et al 17 , which used a decision tree to estimate the proportion of patients experiencing mild and severe spinal cord compression as a result of the testosterone flare associated with LHRH agonist treatment. Patients have a risk of suffering from spinal cord compression in the first cycle of the model and those who experience it are treated with rescue therapies.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations
“…As spinal cord compression is a rare event, data were not available from the trial. Events were incorporated in the same manner as in Lu et al 17 , which used a decision tree to estimate the proportion of patients experiencing mild and severe spinal cord compression as a result of the testosterone flare associated with LHRH agonist treatment. Patients have a risk of suffering from spinal cord compression in the first cycle of the model and those who experience it are treated with rescue therapies.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Consultation with Welsh physicians indicated that rescue therapy would consist of surgery (5% of patients) or radiotherapy (95% of patients). The outcomes of treatment are then modeled (no lasting complications, improvement or paraplegia), with the proportion of patients experiencing each outcome taken from Lu et al 17 .…”
Section: Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the number of patients in that stage may be considerably lower in recent years because many patients are diagnosed and treated earlier in the course of their disease. The rate of spinal cord compression, the most serious adverse event, was estimated to be low (o1%) in the study by Lu et al [18], although admittedly, the true incidence is unknown.…”
Section: Complete Suppression Of Testosterone Surge and Microsurges-imentioning
confidence: 98%